Perception and Attitude of Turkish Gastroenterologists Toward Obesity: A Nationwide Survey Conducted by the Obesity Study Group of the Turkish Gastroenterology Association - Mehmet Tahtacı; Emre Yıldırım; Enver Üçbilek; İlker Şen; Gülden Bilican; Zahide Şimşek; Süheyla Ayça Gümüş; Murat Aladağ; Murat Kıyıcı; Mehmet Cindoruk; Tarkan Karakan (The Turkish Journal of Gastroenterology, 2024)
Background/Aims: Gastroenterologists have an important role in the treatment and management of comorbidities related to obesity. Assessment of gastroenterologists’ perception and attitude toward obesity was aimed in this study.